2020
DOI: 10.5271/sjweh.3920
|View full text |Cite
|
Sign up to set email alerts
|

How to schedule night shift work in order to reduce health and safety risks

Abstract: This Discussion Paper provides scientifically based recommendations on night shift schedules, including consecutive shifts, shift intervals and duration, which may minimize health and safety risks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
81
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 74 publications
(85 citation statements)
references
References 86 publications
2
81
1
1
Order By: Relevance
“…Overall, the current study showed that specific roster characteristics -limited time between shifts (in particular quick returns) and stable or backward rotation -negatively affects sleep problems followed by fatigue (having lower level of energy). In line with the discussion paper by Garde et al (18), optimization of work schedules, ie, meaning more time to recover, forward rotation and potentially less consecutive night shifts are probably helpful to combat the short-term effects but also the long-term health consequences of night work (35)(36)(37).…”
Section: Van De Ven Et Almentioning
confidence: 68%
See 2 more Smart Citations
“…Overall, the current study showed that specific roster characteristics -limited time between shifts (in particular quick returns) and stable or backward rotation -negatively affects sleep problems followed by fatigue (having lower level of energy). In line with the discussion paper by Garde et al (18), optimization of work schedules, ie, meaning more time to recover, forward rotation and potentially less consecutive night shifts are probably helpful to combat the short-term effects but also the long-term health consequences of night work (35)(36)(37).…”
Section: Van De Ven Et Almentioning
confidence: 68%
“…The design of a shift system is one of the key modifiable factors that affects sleep and fatigue (16)(17)(18). Specific roster characteristics such as successive (night) shifts, backward rotation (ie, counterclockwise start times of successive shifts) and quick return to work (ie, limited time between shifts) have been associated with sleep and fatigue (19)(20)(21).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The next characteristic of night shift work that may affect breast cancer risk may be the number of consecutive night shifts. According to previous epidemiological studies, night work lasting ≥3 consecutive nights may increase the risk of breast cancer [ 14 , 15 , 16 , 17 , 18 , 19 ]. Another characteristic of night shift work that may affect breast cancer risk may be the direction of rotation.…”
Section: Introductionmentioning
confidence: 99%
“…t-test or Pearson Chi-square 2 living in the same household 3 more evening type or absolutely evening type4 weekly or more often5 Good subjective health (good or very good)6 Increased need for recovery (6> points).…”
mentioning
confidence: 99%